PENGETAHUAN PERAWAT BERHUBUNGAN DENGAN PELAKSANAAN DISCHARGE PLANNING DI RSUD Dr. M. HAULUSSY AMBON - Dene Fries Sumah; Ritje Andriana Nendissa (2-TRIK: TUNAS-TUNAS RISET KESEHATAN, 2019)
Discharge planning is planning the patient's return, to provide information to patients and their families about things that need to be avoided and carried out in connection with the conditions. Discharge planning written on paper which is the purpose of patient care planning. Discharge planning can motivate patients to achieve recovery, can have an impact on shortening patient care in hospital, lowering the budget for hospital care needs, reducing recurrence rates, and allowing interventions to return plans can be done on time. This study aims to determine the relationship between nurses' knowledge and the implementation of discharge planning in Dr. M. Haulussy Ambon. This study used a cross-sectional design. The sample size of this study was 60 respondents, selected by total sampling technique. Research instruments in the form of questionnaires and observation sheets. The collected data was analyzed by Chi square test. Based on the results of the study note that respondents who had knowledge in the "good" category were 43 people (71.7%) and respondents who had knowledge in the "sufficient" category were 17 people (28.3%). Respondents who carried out discharge planning well were 41 people (68.3%) and respondents who were not good at carrying out discharge planning were 19 people (31.7%). Based on the Chi square test results it was known that the p-value was 0.000, so it could be concluded that there was a relationship between the knowledge of nurses and the implementation of discharge planning in RSUD Dr. M. Haulussy Ambon in 2019. This study recommends the need for discharge planning for patients on a regular basis so that patients are motivated to achieve recovery, as well as a shortening of patient care in the hospital, and it is possible to intervene in a timely discharge plan. Keywords: knowledge; discharge planning ABSTRAK Discharge planning merupakan perencanaan kepulangan pasien, untuk memberikan informasi kepada pasien dan keluarganya tentang hal-hal yang perlu dihindari dan dilakukan sehubungan dengan kondisinya. Discharge planning yang ditulis di kertas yang merupakan tujuan perencanaan perawatan pasien. Discharge planning dapat memberikan motivasi kepada pasien untuk mencapai kesembuhan, dapat memberikan dampak terhadap pemendekan lama perawatan pasien di rumah sakit, menurunkan anggaran kebutuhan perawatan di rumah sakit, menurunkan angka kekambuhan, dan memungkinkan intervensi rencana kepulangan bisa dilakukan tepat waktu. Penelitian ini bertujuan untuk mengetahui hubungan antara pengetahuan perawat dengan pelaksanaan discharge planning di RSUD Dr. M. Haulussy Ambon. Penelitian ini menggunakan desain cross-sectional. Ukuran sampel penelitian ini adalah 60 responden, yang dipilih dengan teknik total Sampling. Instrumen penelitian berupa kuesioner dan lembar observasi. Data yang telah terkumpul dianalisis dengan uji Chi square. Berdasarkan hasil penelitian diketahui bahwa responden yang memiliki pengetahuan dalam kategori “baik” adalah 43 orang (71.7%) dan responden yang memiliki pengetahuan dalam kategori “cukup” adalah 17 orang (28.3%). Responden yang melaksanakan discharge planning dengan baik adalah 41 orang (68.3%) dan responden yang kurang baik dalam melaksanakan discharge planning adalah 19 orang (31.7%). Berdasarkan hasil Chi square test diketahui bahwa p-value adalah 0,000, sehingga dapat disimpulkan bahwa ada hubungan antara pengetahuan perawat dengan pelaksanaan discharge planning di RSUD Dr. M. Haulussy Ambon pada tahun 2019. Penelitian ini merekomendasikan perlunya pelaksanaan discharge planning bagi pasien secara rutin sehingga pasien termotivasi untuk mencapai kesembuhan, serta terjadi pemendekan lama perawatan pasien di rumah sakit, dan dimungkinkan untuk intervensi rencana pulang secara tepat waktu. Kata kunci: pengetahuan; discharge planning